Antibiotics as first-line alternative to appendicectomy in adult appendicitis: 90-day follow-up from a prospective, multicentre cohort study. Issue 11 (3rd September 2021) - Javanmard-Emamghissi, H; Hollyman, M; Boyd-Carson, H; Doleman, B; Adiamah, A; Lund, J N; Moler-Zapata, S; Grieve, R; Moug, S J; Tierney, G M
Abstract: Background: Uncomplicated acute appendicitis can be managed with non-operative (antibiotic) treatment, but laparoscopic appendicectomy remains the first-line management in the UK. During the COVID-19 pandemic the practice altered, with more patients offered antibiotics as treatment. A large-scale observational study was designed comparing operative and non-operative management of appendicitis. The aim of this study was to evaluate 90-day follow-up. Methods: A prospective, cohort study at 97 sites in the UK and Republic of Ireland included adult patients with a clinical or radiological diagnosis of appendicitis that either had surgery or non-operative management. Propensity score matching was conducted using age, sex, BMI, frailty, co-morbidity, Adult Appendicitis Score and C-reactive protein. Outcomes were 90-day treatment failure in the non-operative group, and in the matched groups 30-day complications, length of hospital stay (LOS) and total healthcare costs associated with each treatment. Results: A total of 3420 patients were recorded: 1402 (41 per cent) had initial antibiotic management and 2018 (59 per cent) had appendicectomy. At 90-day follow-up, antibiotics were successful in 80 per cent (1116) of cases. After propensity score matching (2444 patients), fewer overall complications (OR 0.36 (95 per cent c.i. 0.26 to 0.50)) and a shorter median LOS (2.5 versus 3 days, P  < 0.001) were noted in the antibiotic management group. Accounting for interval appendicectomy rates, the mean total cost was €1034 lower per patient managed without surgery. Conclusion: This study found that antibiotics is an alternative first-line treatment for adult acute appendicitis and can lead to cost reductions. Abstract : Adult appendicitis is the most common emergency general surgery condition worldwide, and is normally treated with laparoscopic appendicectomy despite evidence that it can be treated safely with antibiotics. The authors followed up patients who received operative treatment and non-operative treatment with antibiotics during the first wave of the COVID-19 pandemic. Non-operative management was associated with a shorter length of hospital stay, fewer complications and a significant health cost reduction compared with operative management.